Pelaksanaan Pembebasan Bersyarat Bagi Narapidana Penyalahguna Narkotika Di Lembaga Pemasyarakatan Kelas Iia Padang - Rival; Elwidarifa Marwenny (GLOBAL SCIENTS PUBLISHER, 2025)
Parole is one form of integration rights for inmates that allows them to serve the remainder of their prison sentence outside the correctional facility under certain conditions. Narcotics inmates applying for parole have increased in the last 3 (three) years at Class IIA Correctional Facility Padang, even though narcotics crimes are categorized as extraordinary crimes that should receive special attention in both sentencing and correctional processes. This raises concerns that it may weaken efforts to combat narcotics. Integration rights such as parole should be granted with great caution and selectivity. However, this policy tends to become routine without considering its impact on the legal system as a whole. This situation raises concerns about the loose implementation of the parole policy which may blur the essence of the rehabilitation process and weaken the national strategy in combating narcotics. In accordance with Government Regulation Number 99 of 2012 concerning the Requirements and Procedures for the Implementation of the Rights of Correctional Inmates, narcotics inmates can only be granted parole if they meet special requirements, including a willingness to cooperate in uncovering narcotics crime networks. This paper examines two problem formulations, namely: 1) how is the mechanism for parole for narcotics abuse inmates at Class IIA Correctional Facility Padang, 2) can all narcotics inmates be granted parole. To answer these issues, this study uses an empirical juridical approach resulting in the following conclusions: 1) referring to the provisions of the prevailing laws and regulations, namely Law Number 22 of 2022 concerning Corrections and Regulation of the Minister of Law and Human Rights Number 43 of 2021 concerning the Requirements and Procedures for the Granting of Remission, Assimilation, Family Visit Leave, and Parole. The procedure begins with the submission by the concerned inmate, followed by verification and assessment by the correctional officers and the Correctional Observer Team (TPP); 2) all narcotics inmates can be granted parole, namely those who are genuinely active and well-behaved during the rehabilitation process, while those who violate the rules, receive sanctions, and have their parole postponed for 9 (nine) months.